Genetic diversity analysis of hulless barley from Shangri-la region revealed by SSR and AFLP markers - Guo, Y.; Li, Y.; Huang, Y.; Jarvis, D.; Sato, K.; Kato, K.; Tsuyuzaki, H.; Chen, L.; Long, C. (Springer, 2012)
For adding the hulless barley resources of Shangri-la region to the global barley resource library, a basic work was done by us to assess their genetic diversity of this region. The genetic diversity of 60 hulless barley samples collected from three counties in Shangri-la region of Yunnan Province, were studied using SSR (simple sequence repeats) and AFLP (amplified fragment length polymorphism) markers. A total of 70 alleles were detected for 19 pairs of SSR primers, and 525 band containing 464 polymorphic bands were revealed for 5 pairs of AFLP primers. The value of polymorphism information content (PIC) ranged from 0.03 to 0.86 for SSR primers. The total numbers of alleles were 51, 55, 43 in three populations and the polymorphic bands were 188, 205 and 141. The genetic distances and genetic identity among the three populations showed their close relationship. The gene diversity among populations relative to the total population diversity (Gst) was 0.13 for SSR markers and 0.02 for AFLP markers and indicated that just 13 and 2% variations were among populations, respectively. The UPGMA cluster analysis revealed that all of the samples grouped randomly rather than clustered into distinct groups corresponding to their populations, row types and spring/fall types. We concluded that there was high genetic diversity in the population of Shangri-la region and the formation of diversity was related to complex environment and inhabitants traditional practices.